Trapping the substrate radical of heme synthase AhbD - Heidinger, Lorenz; Fix, Isabelle; Friedrich, Thorsten; Layer, Gunhild (Frontiers in Chemistry, 2024)
The heme synthase AhbD catalyzes the last step of the siroheme-dependent heme biosynthesis pathway, which is operative in archaea and sulfate-reducing bacteria. The AhbD-catalyzed reaction consists of the oxidative decarboxylation of two propionate side chains of iron-coproporphyrin III to the corresponding vinyl groups of heme b. AhbD is a Radical SAM enzyme employing radical chemistry to achieve the decarboxylation reaction. Previously, it was proposed that the central iron ion of the substrate iron-coproporphyrin III participates in the reaction by enabling electron transfer from the initially formed substrate radical to an iron-sulfur cluster in AhbD. In this study, we investigated the substrate radical that is formed during AhbD catalysis. While the iron-coproporphyrinyl radical was not detected by electron paramagnetic resonance (EPR) spectroscopy, trapping and visualization of the substrate radical was successful by employing substrate analogs such as coproporphyrin III and zinc-coproporphyrin III. The radical signals detected by EPR were analyzed by simulations based on density functional theory (DFT) calculations. The observed radical species on the substrate analogs indicate that hydrogen atom abstraction takes place at the -position of the propionate side chain and that an electron donating ligand is located in proximity to the central metal ion of the porphyrin.